An IoT-Based Smart Airport Check-In System Via Three-Factor Authentication (3FA) - Ashna Sahdi Ali; Dler Salih Hasan (Zanco Journal of Pure and Applied Sciences, 2023)
The Internet of Things (IoT) has been taking over the globe, providing an interface where computer devices are connected to digital equipment, mechanical machines, and even individuals. This paper suggests a smart airport check-in system utilizing the Internet of Things. The system includes setting up a smart door to secure the passage to travelers at the airport, depending on the barcode boarding pass (BCBP). The door is designed and implemented by using Raspberry Pi 4B, and two cameras are installed. The first one is for scanning the BCBP, decoding a developed portable data file (PDF417)-based algorithm and processing the data. The second camera is to detect and capture traveler’s faces in real-time video streaming among face alignment using Dlib and OpenCV-Python algorithms. A fingerprint reader is also attached to the system as biometric authentication. The system is monitored by using the KAA platform. When the data of a traveler is verified and matched, the door opens. If the data is not matched, the door remains closed and a Telegram notification will be sent to the airport security. The system was tested on 100 travelers. It resulted to obtain smooth, secure, and reliable check-ins. In terms of efficiency, our system has decreased maximum and minimum time to check-in for each passenger to a much larger extent comparing to the traditional check-in system.